Schematic Structure of Manifesto Launch Speeches of Three Political Parties - Afful, Joseph Benjamin Archibald; Gyasi, Rexford Boateng (Advances in Social Sciences Research Journal, 2021)
A key pre-election spoken genre in several modern democracies is unarguably the manifesto launch speech. Yet, it has surprisingly received either very little or no scholarly attention. Consequently, from a rhetorical perspective, this study examined the schematic structure of three keynote speeches delivered by presidential aspirants of three leading political parties in Ghana – New Patriotic Party (NPP), National Democratic Congress (NDC), and the Convention People’s Party (CPP) – to launch their political parties’ manifestos in 2016. The three speeches delivered by the presidential candidates of the three parties constituted the data set for the study. Applying the popular Swalesean rhetorical move analysis, originally meant for the academic setting, the study identified the use of a nine-move pattern as the schematic structure for the genre across the three speeches, with four ambiguous moves. These findings of the study have implication for the standardizing of the schematic structure of manifesto launch speeches worldwide and, thus, contributes to the scholarship on the political manifesto genre, political communication as well as further research on manifesto launch speeches in other democracies around the world.